The Effect of Attitude and Trust on Behavioral Intention In The Modern Market Industry - Hafiz Jodith Arfansyah; Endy Gunanto Marsasi (Jurnal Economic Resource, 2023)
This research gap is the relationship between trust and behavioral intention. Trust will be an element of novelty in this study that affects behavioral intention. This research is based on the Theory of Reasoned Action, which explains attitudes, which are influenced by subjective norms and determine behavior. This research aims to assess the effect of the relationship between hypotheses in the modern market industry, especially minimarkets. It used the structural equation modeling (SEM) method to distribute samples from a total of 245 respondents in the questionnaire. The testing was done using the IBM SPSS 25 program and SEM-AMOS 24 software. The results of this study indicate the rejection of one hypothesis that connects the influence of Smart Shopper Self Perception on behavioral intention in customers in the modern market industry, namely minimarkets.